2002
DOI: 10.1051/gse:2002029
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of aphidicolin-induced break points in Holstein-Friesian cattle (Bos taurus) using RBG-banding

Abstract: -Fragile sites (FS) seem to play a role in genome instability and may be involved in karyotype evolution and chromosome aberrations. The majority of common fragile sites are induced by aphidicolin. Aphidicolin was used at two different concentrations (0.15 and 0.30 µM) to study the occurrence of FS in the cattle karyotype. In this paper, a map of aphidicolin induced break points and fragile sites in cattle chromosomes was constructed. The statistical analysis indicated that any band with three or more breaks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
1
5
2
1
Order By: Relevance
“…0.01). This is in contrast with previous observations in pigs by Riggs et al (1993) and in cattle by Rodriguez et al (2002) who reported variations among animals due to an 'animal effect' rather than by gender. In the present study, the yield of breakages per chromosome was found to be significantly different 'among' the chromosomes within the karyotype thus indicating a 'nonrandom' expression.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…0.01). This is in contrast with previous observations in pigs by Riggs et al (1993) and in cattle by Rodriguez et al (2002) who reported variations among animals due to an 'animal effect' rather than by gender. In the present study, the yield of breakages per chromosome was found to be significantly different 'among' the chromosomes within the karyotype thus indicating a 'nonrandom' expression.…”
Section: Discussioncontrasting
confidence: 56%
“…By comparing the present results with those reported in cattle by Rodriguez et al (2002), obtained under the same experimental conditions, we observe a complete lack of homology in the location of fragile sites between the two species. While in river buffalo the most fragile band has been found on chromosome 9q213 with 24 breakages out of 400 (6%), followed by chromosome 19q21 with 16 (4%), chromosome 17q21 and inacXq24 with 15 (3.75%), in cattle the most fragile bands have been found in totally different non-homologous chromosomes, such as 1q13 and Xq31, with 14 breakages out of 217 (6.45%), followed by chromosome 1q21 with 11 (5.0%), 3q22 and 5q32 with 9 (4.1%).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations